Desain Didaktis Penjumlahan dan Pengurangan Pecahan Campuran di Sekolah Dasar - Irfan Fauzi; Ririn Arini (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
This research was motivated by the students' learning obstacle in understanding the addition and subtraction of mixed fractions. So this research aims to develop a didactic design on the addition and subtraction of mixed fractions in grade 5 elementary schools based on student learning trajectories and can improve students' learning obstacles on addition and subtraction of mixed fractions. This research used the Didactical Design Research (DDR) method in one of the elementary schools in Bandung, with the subjects being 30 students in grade 5 and 29 students in grade 6. The data collection techniques used tests, interview, document analysis, focus group discussion (FGD), and observation. The results of this research indicated that the Didactic Design has a positive impact on student understanding and reduces the students' learning obstacles which are ontogenic, epistemological and didactical on the addition and subtraction of mixed fractions. Then, the average score of the students after the didactic design implementation was 75.3. This research is expected to be a reference for teachers in developing didactic designs for learning mathematics, especially fraction material in elementary schools using Didactical Design Research (DDR).